Pengaruh Literasi Keuangan dan Kemudahan Paylater Terhadap Perilaku Keuangan Pada Generasi Z di Kota Bandung - Rahmania, Faza; Manjaleni, Rola (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Technological advances from generation to generation have connected various aspects of life, including in terms of providing basic needs that can now be accessed more quickly. One of the impacts is the transformation of the function of money and the emergence of new payment methods such as paylater. Paylater is present as an alternative solution for individuals who have financial limitations but need goods or services instantly. This convenience, although it provides practical benefits, has the potential to trigger unhealthy financial behavior, especially among Generation Z who tend to be consumptive. The mismatch between income and expenses can lead to dependence on digital loans. Therefore, financial literacy skills are important to help individuals understand the risks and benefits of using paylater wisely. This study aims to determine the effect of financial literacy and the convenience of paylater on the financial behavior of Generation Z in Bandung City. This study uses a quantitative approach with a survey method through a questionnaire distributed to 100 Generation Z respondents who are active paylater users. The sampling technique uses purposive sampling. The results of the study indicate that both financial literacy and ease of paylater have a significant effect on financial behavior with a significance value of 0.000 (<0.05) and a calculated t value> t table (1.660). Data analysis techniques used include classical assumption tests, multiple linear regression, t tests, f tests, and coefficients of determination.